Immunosuppressive Drug‐Resistant Armored T‐Cell Receptor T Cells for Immune Therapy of HCC in Liver Transplant Patients. Issue 1 (2nd June 2021) - Hafezi, Morteza; Lin, Meiyin; Chia, Adeline; Chua, Alicia; Ho, Zi Zong; Fam, Royce; Tan, Damien; Aw, Joey; Pavesi, Andrea; Krishnamoorthy, Thinesh Lee; Chow, Wan Cheng; Chen, Wenjie; et al.
Abstract : Background and Aims: HBV‐specific T‐cell receptor (HBV‐TCR) engineered T cells have the potential for treating HCC relapses after liver transplantation, but their efficacy can be hampered by the concomitant immunosuppressive treatment required to prevent graft rejection. Our aim is to molecularly engineer TCR‐T cells that could retain their polyfunctionality in such patients while minimizing the associated risk of organ rejection. Approach and Results: We first analyzed how immunosuppressive drugs can interfere with the in vivo function of TCR‐T cells in liver transplanted patients with HBV‐HCC recurrence receiving HBV‐TCR T cells and in vitro in the presence of clinically relevant concentrations of immunosuppressive tacrolimus (TAC) and mycophenolate mofetil (MMF). Immunosuppressive Drug Resistant Armored TCR‐T cells of desired specificity (HBV or Epstein‐Barr virus) were then engineered by concomitantly electroporating mRNA encoding specific TCRs and mutated variants of calcineurin B (CnB) and inosine‐5′‐monophosphate dehydrogenase (IMPDH), and their function was assessed through intracellular cytokine staining and cytotoxicity assays in the presence of TAC and MMF. Liver transplanted HBV‐HCC patients receiving different immunosuppressant drugs exhibited varying levels of activated (CD39 + Ki67 + ) peripheral blood mononuclear cells after HBV‐TCR T‐cell infusions that positively correlate with clinical efficacy. In vitro experiments with TAC and MMF showed a potent inhibition of TCR‐T cell polyfunctionality. This inhibition can be effectively negated by the transient overexpression of mutated variants of CnB and IMPDH. Importantly, the resistance only lasted for 3‐5 days, after which sensitivity was restored. Conclusions: We engineered TCR‐T cells of desired specificities that transiently escape the immunosuppressive effects of TAC and MMF. This finding has important clinical applications for the treatment of HBV‐HCC relapses and other pathologies occurring in organ transplanted patients.